Study of the influence of GLP-1 receptor agonists on the metabolic activity of the intestinal microbiota in patients with type 2 DM - Zinych, Olesia; Stepanov, Yurii; Shyshkan-Shyshova, Kateryna; Klenina, Inna; Kushnarova, Nataliia; Kovalchuk, Alla; Prybyla, Olha (ScienceRise: Medical Science, 2023)
The aim: to investigate the peculiarities of the metabolic activity of the intestinal microbiota in patients with type 2 diabetes under the influence of glucagon-like peptide-1 receptor agonist therapy. Materials and methods: 21 patients with type 2 diabetes mellitus were included in the study, the average age was 57.2±8.53 years (M±SD), the HbA1c level was 8.29±0.88 % (M±SD). Patients were prescribed raGLP-1 at the maximum tolerated dose for 6 months. Before and after the course of treatment, indicators of body composition were determined by the bioelectrical impedance method (TANITA BC-545N analyzer, Japan), characteristics of carbohydrate metabolism and the lipid spectrum of blood serum, as well as the concentration of GLP-1, trimethylamine-N-oxide (TMAO) by the immunoenzymatic method, of short-chain fatty acids (SCFA) by the method of chromatographic research. Results. After 6 months of therapy with liraglutide against the background of a statistically significant decrease in fasting blood glucose and HbA1c levels (p<0.05), a decrease in body mass index and waist circumference (p<0.05), a decrease in the content of visceral (p<0.05 ) and total fat (p<0.05) in patients with type 2 diabetes, there was a decrease in the concentration of TMAO in blood serum (p<0.05) and an increase in the concentration of SCFA: acetic, propionic (p<0.05) in the coprofiltrate and a tendency to increase in the level of butyric acids. Data analysis also established an increase in the concentration of endogenous GLP-1 in the blood (p<0.05). Conclusions. The detected changes in microbial metabolites may indicate a positive effect of raGLP-1 on the composition of the intestinal microbiota and its metabolic activity in patients with T2DM, which in turn contributes to the improvement of endogenous secretion of incretins